Risk Perception, Gender, dan Pengetahuan Investasi pada Niat Berinvestasi - Dewi, Luh Gede Krisna; Latrini, Made Yenni; Penindra, I Made Dwi Budiana (E-Jurnal Akuntansi; Vol 31 No 11 (2021)DO - 10.24843/EJA.2021.v31.i11.p18, 2021)
This study aims to analyze the effect of risk perception, gender, and investment knowledge on the investment intentions of accounting students. The research was conducted at Universities/Polytechnics/ State and Private Colleges of Bali Province with a total sample of 270 students. Sampling method using purposive sampling method. The analysis technique used is multiple linear regression using a questionnaire instrument. The results showed that risk perception and investment knowledge had a positive effect while gender had a negative effect on the investment intentions of accounting students. The implication of this research supports the Theory of Planned Behavior which states that personal, social and informational aspects shape attitudes, subjective norms, perceptions of control in encouraging accounting students' investment intentions. Practical implications of research for educational institutions to develop education in the field of investment. Keywords : Risk Perception; Gender; Investment Knowledge; Intention to Invest.